Digital media, creativity, and marketing, within the scope of the contemporary instant culture - Vidaković, Mira; Vidaković, Dario (Anali Ekonomskog fakulteta u Subotici, 2020)
Contemporary culture is often characterized as the ’’instant culture’’, in which new mobile technologies and social nature of Web 2.0 enable individuals’ continual access to seemingly unlimited scope of information and media content, no matter where they are. This creates a channel through which these individuals become constantly available for interaction, therefore by creating digital content it is now possible to engage them, in such a way that this interaction will not disturb their everyday habits and behavior in using digital media. That is where content marketing is created: a tool which strives to engage individuals through media content that will create a certain value for the consumer. Since content marketing demands quality and creative content that also has certain marketing purpose, here arises the question of the integrity of such creative process. Marketing activity, journalism, and creativity must be driven by certain ethical codes, which will insure the truthfulness, honesty, and safety of the interaction between the consumers and the creators of media content. This paper strives to divulge ethical ambiguities in content marketing, emphasizing truthfulness and transparency as key factors of its success as a tool in digital marketing, while also accentuating the importance of creating valuable and quality content for further evolution of this variety of expression through digital media.